Expressing p20 hairpin RNA of Citrus tristeza virus confers Citrus aurantium with tolerance/resistance against stem pitting and seedling yellow CTV strains - Chun-zhen CHENG; Jia-wei YANG; Hu-bin YAN; Xue-jun BEI; Yong-yan ZHANG; Zhi-ming LU; Guang-yan ZHONG (Journal of Integrative Agriculture, 2015)
The Citrus tristeza virus (CTV) uses 3 silencing suppressor genes, p20, p23 and p25, to resist the attacks from its Citrus hosts. Inactivating these genes is therefore obviously a potential defensive option in addition to the current control strategies including aphid management and the use of mild strain cross protection. In this study, we cloned partial DNA fragments from the three genes, and used them to construct vectors for expressing hairpin RNAs (hpRNAs). To facilitate the formation of hpRNAs, the constructs were introduced in a loop structure. Following transformation of sour orange (Citrus aurantium) with these constructs, 8 p20 hpRNA (hp20) and 1 p25 hpRNA (hp25) expressing lines were obtained. The 7 hp20 transgenic lines were further characterized. Their reactions to CTV were tested following inoculation with CT14A and/or TR-L514, both of which are severe strains. Results showed that 3 lines (hp20-5, hp20-6 and hp20-8) were completely resistant to TR-L514 under greenhouse conditions for no detectable viral load was found in their leaves by PCR. However, they exhibited only partial suppression of TR-L514 under screen house conditions since the virus was detected in their leaves, though 2 months later compared to non-transgenic controls. Further tests showed that hp20-5 was tolerant also to CT14A under screen house conditions. The growth of hp20-5 was much better than others including the controls that were concurrently challenged with CT14A. These results showed that expressing p20 hpRNA was sufficient to confer sour orange with CTV resistance/tolerance.